Mechanized endodontic treatment in deciduous dentition (Research, Society and Development, 2021)
Mechanized instrumentation in permanent teeth is already a well-established and widely used practice in dentistry today. Several studies show considerable advantages when compared to the manual instrumentation technique, among them one can consider the reduction of surgical time and less discomfort to the patient during and after the procedure. Although the cost is considerably higher when compared to the treatment performed with manual instrumentation, this is justifiable. However, mechanized endodontics for endodontic treatments in pediatric dentistry is still questionable. The objective of this literature review was to identify advantages and disadvantages of the mechanized endodontic procedure in pediatric dentistry. Therefore, we carried out a bibliographic survey, considering publications from 2015 to 2020 on the PubMed, Google Scholar, Scielo, Springer and Cochrane platforms. Seventeen articles were selected, including in vitro studies, systematic reviews, and randomized studies and two bibliographic references, the Pediatric Dentistry Manual (Guedes-Pinto, 2012) and the manual “Guidelines for Clinical Procedures in Pediatric Dentistry – ABO”, released in 2020. After screening the materials, 8 articles, the Pediatric Dentistry Manual (Guedes-Pinto) and the ABO Manual were included in this review. It was concluded that, despite the significant benefits presented by mechanized instrumentation in permanent teeth, no advantages of the technique were observed when applied in pediatric dentistry, unjustifying the high investment.